Bioinformatics insights into the role of GFPT1 in breast invasive carcinoma: implications for tumor prognosis, immune modulation, and therapeutic applications - Liang, Jianghui; Deng, Xiaolian; Zhang, Yingyi; Fei, Tianchi; Ouyang, Muzi; Yu, Chengjie; Xiang, Yang; Jia, Dongwei; Duan, Fangfang (Frontiers in Genetics, 2024)
BackgroundMetabolic reprogramming is a hallmark of cancer, including alterations in the hexosamine biosynthesis pathway (HBP). Glutamine-fructose-6-phosphate transaminase 1 (GFPT1) is the key regulatory enzyme in the HBP; however, its role in invasive breast carcinoma remains underexplored.MethodsThis study utilized integrated data from The Cancer Genome Atlas (TCGA) to assess GFPT1 expression in breast cancer (BRCA) patients. Functional enrichment and mutational landscape analyses were performed, along with chemosensitivity predictions. In vitro experiments were conducted by silencing GFPT1 in malignant breast epithelial cells to evaluate changes in proliferation, migration, and apoptosis.ResultsElevated GFPT1 expression was linked to advanced-stage breast cancer and identified as an independent prognostic marker for overall survival (OS). High GFPT1 levels were associated with increased cytoplasmic translation, activation of oncogenic pathways, and infiltration of M2 macrophages. The GFPT1-High group also showed a higher mutational burden, with frequent TP53 mutations. Chemosensitivity analysis revealed increased IC50 values for chemotherapy drugs in this group. GFPT1 silencing led to reduced cell proliferation and migration, along with enhanced apoptosis.ConclusionThese findings indicate that GFPT1 is a novel prognostic biomarker and a predictive indicator of chemotherapy response in invasive breast carcinoma. GFPT1 influences mRNA translation, cell cycle regulation, and M2 macrophage infiltration, thereby promoting cancer cell proliferation and metastasis.